2009
DOI: 10.1111/j.1432-2277.2009.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in the patient with hepatitis C

Abstract: Summary Hepatitis C virus (HCV) infection is the most frequent cause of liver disease after renal transplantation. Its clinical course is irrelevant in the short term, except for rare cases of fibrosing cholestatic hepatitis. However, in the long run, HCV infection can lead to major liver complications. Because interferon (IFN) is generally contraindicated in renal transplant patients, the best approach is to treat patients on dialysis. Until more information with pegylated‐IFN is available, the use of alpha‐I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 117 publications
(293 reference statements)
0
35
1
Order By: Relevance
“…In contrast, deaths from infectious complications in the waiting list patients were lower when compared with the kidney transplant recipients (20% vs. 40.5%) (25). The results from our and prior studies (26,27) suggest more efforts to reduce infectious complications after kidney transplantation are required.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, deaths from infectious complications in the waiting list patients were lower when compared with the kidney transplant recipients (20% vs. 40.5%) (25). The results from our and prior studies (26,27) suggest more efforts to reduce infectious complications after kidney transplantation are required.…”
Section: Discussioncontrasting
confidence: 77%
“…Ribavirin is generally contraindicated in renal failure because of the risk for hemolytic anemia, and there is insufficient data on newer protease inhibitor treatments in patients with renal failure. Patients with a sustained virologic response to pretransplant treatment with interferon have a reduced risk for HCV recurrence and decreased post-transplant GN (60). IFNa is associated with an increased risk for allograft dysfunction and rejection, making post-transplant treatment more difficult.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…This agrees the majority of published short-term series [27][28][29] and long-term ones. 20,30 Conversely, her short-term 26 and long-term studies 18,23 have demonstrated significantly inferior graft survival in viremic recipients. Other studies document lower graft survival in nonviremic recipients.…”
Section: Discussionmentioning
confidence: 99%
“…viremic group. 23,24 Also Baid-Agrawal 25 suggests that impaired peripheral insulin sensitivity is associated with HCV infection irrespective of the transplant status, and is the most likely pathogenic mechanism involved in the development of type 2 diabetes mellitus associated with HCV infection. This variation in reported incidence may be related to the varying definitions of diabetes used in the literature, duration of follow-up, presence of other modifiable, and nonmodifiable risk factors.…”
Section: Discussionmentioning
confidence: 99%